2002
DOI: 10.1172/jci0214574
|View full text |Cite
|
Sign up to set email alerts
|

IL-15, a survival factor for kidney epithelial cells, counteracts apoptosis and inflammation during nephritis

Abstract: IL-15, a T cell growth factor, has been linked to exacerbating autoimmune diseases and allograft rejection. To test the hypothesis that IL-15-deficient (IL-15-/-) mice would be protected from T cell-dependent nephritis, we induced nephrotoxic serum nephritis (NSN) in IL-15-/and wild-type (IL-15 +/+) C57BL/6 mice. Contrary to our expectations, IL-15 protects the kidney during this T cell-dependent immunologic insult. Tubular, interstitial, and glomerular pathology and renal function are worse in IL-15-/mice dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
53
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 53 publications
8
53
0
Order By: Relevance
“…The human epithelial cells of various tissues produce IL-15, which acts not only on immune cells (e.g., IELs in the gut), but also on epithelial cells, mainly via its anti-apoptotic action [17], [18], [19], [20]. Thus, it was shown that human and mouse renal tubular epithelial cells (RPTEC) constitutively express the receptor IL-15Rαβγ [15] and secrete the cytokine IL-15 [21], which plays an important role in renal physiology as an autocrine survival factor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The human epithelial cells of various tissues produce IL-15, which acts not only on immune cells (e.g., IELs in the gut), but also on epithelial cells, mainly via its anti-apoptotic action [17], [18], [19], [20]. Thus, it was shown that human and mouse renal tubular epithelial cells (RPTEC) constitutively express the receptor IL-15Rαβγ [15] and secrete the cytokine IL-15 [21], which plays an important role in renal physiology as an autocrine survival factor.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it was shown that human and mouse renal tubular epithelial cells (RPTEC) constitutively express the receptor IL-15Rαβγ [15] and secrete the cytokine IL-15 [21], which plays an important role in renal physiology as an autocrine survival factor. Indeed, increased sensitivity of cells to apoptosis is observed in the damaged kidney of IL-15−/−, IL-15Rα−/− knockout mice or during acute renal injury induced by different protocols that induce a decrease in IL-15 production by epithelial cells [20], [22]. IL-15 enhances intestinal barrier function by promoting the formation of tight junctions between epithelial cells [23].…”
Section: Introductionmentioning
confidence: 99%
“…24 Moreover, IL-15 signaling has been shown to function as a protective agent against cell death in several immune and non-immune cell types. 11, 14 These studies indicate that the protective capacity of IL-15 is underpinned by the ability of the IL-15 receptor complex to activate pro-survival pathways. 25 To this end, each receptor subunit within the IL-15R complex has a distinct binding and signaling capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been shown to protect against cell death in several non-immune cell types. 12, 14 IL-15 inhibits TNF-alpha mediated apoptosis within L929 murine fibroblasts, 15 and functions as a pro-survival autocrine factor in renal epithelial cells 14 and murine microglia. 12 To reduce apoptosis IL-15 signals though the IL-15 receptor system.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, IL-15 was shown to induce differentiation of CD105 + renal CSCs isolated from human renal carcinomas (Azzi et al, 2011). Based on previous studies that had shown that IL-15 acted as a survival factor in renal tubular epithelial cells via autocrine-paracrine loops, the authors identified IL-15 as a potential candidate (Shinozaki et al, 2002). Other studies have shown that IL-15 upregulates E-cadherin expression through γc chain signaling pathway and blocks EMT in renal tubular epithelial cells ( Figure 2 ) (Giron-Michel et al, 2012, 2013).…”
Section: Interleukinsmentioning
confidence: 99%